One-pot d-lactic acid production using undetoxified acid-pretreated corncob slurry by an adapted Pediococcus acidilactici. (November 2022) - Qiu, Zhongyang; Han, Xushen; He, Jianlong; Jiang, Yanan; Wang, Guangli; Wang, Zejia; Liu, Xiaoyan; Xia, Jun; Xu, Ning; He, Aiyong; Gu, Hanqi; Xu, Jiaxing
Graphical abstract: Highlights: A robust d -lactic acid producing strain was obtained after adaptive evolution. Adapted strain had far higher inhibitors tolerance and conversion capacities. One-pot SSCF was conducted using undetoxified whole slurry of pretreated corncob. 61.9 g/L d -lactic acid was produced with the overall yield of 0.48 g/g dry corncob. Abstract: Inhibitor tolerance is still a bottleneck for lactic acid bacteria in lignocellulose biorefinery, while it is hard to obtain one engineered strain with strong tolerance to all inhibitors. Herein, a robust adapted d -lactic acid producing strain Pediococcus acidilactici XH11 was obtained by 111 days' long-term adaptive evolution in undetoxified corncob prehydrolysates. The adapted strain had higher inhibitors tolerance compared to the parental strain, primarily due to its increased conversion capacities of four typical aldehyde inhibitors (furfural, HMF, vanillin, and 4-hydroxybenzaldehyde). One-pot simultaneous saccharification and co-fermentation was successfully achieved using the whole slurry of acid-pretreated corncob without solid–liquid separation and detoxification, by applying the adapted P. acidilactici XH11. Finally, 61.9 g/L of d -lactic acid was generated after 96 h' fermentation (xylose conversion of 89.9 %) with the overall yield of 0.48 g/g dry corncob. This study gave an important option for screening of industrial strains in cellulosic lactic acid production processes.